Perceptions of Stunting: Negotiating Local and Medical Knowledge in Jeneponto, South Sulawesi - Nurlela, Andi; Muhammad, Sawedi; Arifin, Suryanto; Hariashari, Hariashari (Universitas Muhammadiyah Sorong, 2025)
The problem of stunting is still a complex social and health issue in Indonesia, including in Jeneponto Regency, South Sulawesi, which has the highest prevalence of stunting in the province. People in this region have a different understanding of the concept of stunting compared to the medical definition used by the government. This research aims to analyze how the people of Jeneponto build an understanding of stunting through negotiations between local knowledge and medical knowledge. The research uses a qualitative approach with phenomenological design. A total of 15 informants were selected purposively, consisting of parents of children under five, health workers, posyandu cadres, community leaders, and local government officials. Data were collected through in-depth interviews, participatory observations, and documentation studies, then analyzed inductively using manual coding techniques. The results of the study show that people do not view stunting as a health problem, but as a social opportunity to obtain nutritional assistance and economic support. The label